The Effect Of Audit Fees And Audit Opinions Which Are Moderated By The Role Of Women On The Board Of Directors On Corporate Tax Avoidance - Sherly Sherly (Universitas Internasional Batam, 2024)
This study aims to ascertain the impact of women in board who moderate the relationship between audit fees and audit opinion on corporate tax avoidance. In total, 120 non-financial firms listed on the Indonesia Stock Exchange between 2017–2021 matched the criteria for the study and served as research samples. Panel data regression was the method of data analysis used in this study. According to the study's findings, there is no impact between audit fees and audit opinion on tax avoidance practices. The results also show the same thing for audit fees and audit opinion which are moderated by the role of women in board, which has no impact on tax avoidance practices. The results of this study should be able to help academics and other researchers in determining the effect of audit fees and audit opinion on corporate tax avoidance moderated by the role of women in board